2014
DOI: 10.1038/npp.2014.184
|View full text |Cite
|
Sign up to set email alerts
|

Losing Control Under Ketamine: Suppressed Cortico-Hippocampal Drive Following Acute Ketamine in Rats

Abstract: Systemic doses of the psychotomimetic ketamine alter the spectral characteristics of hippocampal and prefrontal cortical network activity. Using dynamic causal modeling (DCM) of cross-spectral densities, we quantify the putative synaptic mechanisms underlying ketamine effects in terms of changes in directed, effective connectivity between dorsal hippocampus and medial prefrontal (dCA1-mPFC) cortex of freely moving rats. We parameterize dose-dependent changes in spectral signatures of dCA1-mPFC local field pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 75 publications
2
69
0
Order By: Relevance
“…This is in accordance with the higher expression of NMDA receptors in the dorsal hippocampus along a ventral-dorsal axis in both species (Strange et al 2014). In rats, ketamine has been recently shown (Moran et al 2015) to suppress the drive from the medial prefrontal cortex (mPFC) to dorsal CA1 (dCA1) through NMDA receptors, while enhancing dCA1-to-mPFC drive through AMPA receptors, which for our study could imply that the direction for the observed increase in coupling came from the dorsal hippocampus, via subiculum outputs. In this respect, we have also accumulated substantial evidence that PFC-HC drive is mediated via AMPA receptors mediating long-term potentiation (LTP).…”
Section: Hippocampal and Prefrontal Pathophysiologymentioning
confidence: 65%
“…This is in accordance with the higher expression of NMDA receptors in the dorsal hippocampus along a ventral-dorsal axis in both species (Strange et al 2014). In rats, ketamine has been recently shown (Moran et al 2015) to suppress the drive from the medial prefrontal cortex (mPFC) to dorsal CA1 (dCA1) through NMDA receptors, while enhancing dCA1-to-mPFC drive through AMPA receptors, which for our study could imply that the direction for the observed increase in coupling came from the dorsal hippocampus, via subiculum outputs. In this respect, we have also accumulated substantial evidence that PFC-HC drive is mediated via AMPA receptors mediating long-term potentiation (LTP).…”
Section: Hippocampal and Prefrontal Pathophysiologymentioning
confidence: 65%
“…A parsimonious explanation follows from 446 447 448 449 450 451 452 453 454 455 456 457 458 459 460 461 462 463 464 465 466 467 468 469 470 471 472 473 474 475 476 477 478 479 480 481 482 483 484 485 486 487 488 489 490 491 492 493 494 495 496 497 498 499 500 501 502 503 504 505 506 507 508 509 510 511 512 513 514 515 516 517 518 519 520 521 522 523 524 525 526 527 528 529 530 531 532 533 534 535 536 537 538 539 540 541 542 543 544 545 546 547 548 549 550 551 552 553 554 555 556 557 558 559 560 561 562 563 564 565 evidence that in visual cortex, NMDA receptors facilitate modulatory feedback through lateral connections, while AMPA underlies feedforward processes (46). Preclinical research has shown that ketamine-induced NMDA blockade is associated with disinhibition of glutamate release and consequent activation of AMPA receptors (64,65). Furthermore, one parsimonious explanation is that NMDA hypofunction causes a disruption in the excitatory (glutamate) and inhibitory (gamma-aminobutyric acid) balance in the neural circuitry (37,66).…”
Section: P100 Effectmentioning
confidence: 99%
“…Pal et al (74) recently reported a global reduction in long-range cortical gamma coherence after the infusion of ketamine that was reversible after the termination of the anesthetic. Ketamine has also been shown to suppress top-down effective connectivity, as determined by dynamic causal modeling, between medial prefrontal cortex and dorsal hippocampus (75). …”
Section: Anesthetic-mediated Disruption Of Recurrent Processing In Anmentioning
confidence: 99%